How Does the Short-Term Training Program Contribute to Skills Development in Bangladesh? : A Tracer Study of the Short-Term Training Graduates - World Bank (World Bank, Washington, DC, 2016)
Skills development is one of the priorities for national economic development strategies of Bangladesh. The vision 2021 of the Government of Bangladesh gives the highest priority to building a large base of skilled workers in order to achieve a poverty-free middle-income country by 2021. The skills development sector is highly complex due to multiple service providers, a vast spectrum of target audiences, a large range in modalities of service provision, and varied emphases in terms of skills levels and types. The short-term training, a formal channel of six months training, is an important instrument for bridging the gap between the needs of the labor market for increasing the pool of skillful workers and the aspiration of the students for finding a good job. In order to assess the performance of short-term training and interventions by Skills and Training Enhancement Project (STEP), a tracer study was conducted between December 2013 and January 2014. Skills and Training Enhancement Project (STEP) is jointly financed by the World Bank, Canada and the Government of Bangladesh (GoB), which started in 2010 for contributing to Bangladesh’s medium to long-term objective of developing its human resources as a cornerstone of its strategy for poverty alleviation and economic growth. It supports competitively selected 42 public and 8 private short-term training institutions for improving the quality of training and providing opportunities to the disadvantaged youth for obtaining skills from the select training providers.